The evaluation of the efficiency of transport and logistics infrastructure of railway transport - Saparovna Mukhtarova, Karlygash (Array, 2018)
The high level of logistics development positively affects many socio-economic indicators of the country’s economic development, such as inflation rates, productivity indicators, etc. Increasing productivity through the use of logistics at enterprises has a positive impact on the competitiveness in global markets, as well as on profit level. The aim of this article is to analyze the evolution of productivity in rail transport among several countries from 1997 to 2016. We use a non-parametric approach that allows us to change the performance and efficiency of the transport infrastructure. The main indicators of rail transport should be divided into variations of efficiency and technical changes. The results indicate that productivity growth is concentrated in the last period (1997-2016), when most countries conducted reform processes. This increase in productivity occurred mainly due to technical progress. We also analyze the correlation analysis to determine the factors most influencing the effectiveness. In contrast to similar articles, we justified that the higher the autonomy and financial independence, the higher the level of efficiency and technical change in the infrastructure of the railway transport.